PERKAWINAN SIRI DAN PENGARUHNYA TERHADAP HAK ASUH ANAK DITINJAU DARI PERSPEKTIF PERADILAN AGAMA - Rofiq, Nur; nurzahrah, yasmin; Solahudin, Irawan; Hikmah, Annisa Nur; Aziz, Dani Safangaturrahman; Bily, Muhammad Yusuf Arda (Wahana Islamika: Jurnal Studi Keislaman, 2024)
Problems that arise as a result of divorce from unregistered marriages have an impact on children's rights, including custody, because unregistered marriages have no validity in the eyes of the law. The aim of this research is to determine the legality of unregistered marriages religiously and juridically and its impact on children. This research is a literature review using triangular data analysis techniques and expert opinion. Data collection was carried out using the literature study method, namely collecting information from journals, websites and statutory regulations. The data source used is primary data, namely a journal written by Dwi Nur Kasanah and Ahmad Faruq with the title Siri Marriage Divorce and its Effect on Children's Rights in the Mojokerto Religious Courts and secondary data used is a journal written by Siti Ummu Adillah with the title Legal Implications of Siri Marriages Against Women and Children, Marriage Laws, Compilation of Islamic Law and other supporting literature. The research results obtained were 1) the factors behind the occurrence of unregistered marriages, namely economic factors, customs/customs, the legal age limit for marriage, pregnancy outside of marriage, and lack of knowledge regarding the urgency of registering a marriage. 2) the civil relations of children resulting from unregistered marriages are limited to their mothers and are further regulated in Constitutional Court Decision No.46/PUU-VIII/2010. 3) the judge's considerations in granting custody of children born from unregistered marriages will prioritize the interests and good of the child for the future.